Glycogen Synthase Kinase-3 Regulates Production of Amyloid-β Peptides and Tau Phosphorylation in Diabetic Rat Brain - Zhong-Sen Qu; Liang Li; Xiao-Jiang Sun; Yu-Wu Zhao; Jin Zhang; Zhi Geng; Jian-Liang Fu; Qing-Guo Ren (The Scientific World Journal, 2014)
The pathogenesis of diabetic neurological complications is not fully understood. Diabetes mellitus (DM) and Alzheimer’s disease (AD) are characterized by amyloid deposits. Glycogen synthase kinase-3 (GSK-3) plays an important role in the pathogenesis of AD and DM. Here we tried to investigate the production of amyloid-β peptides (Aβ) and phosphorylation of microtubule-associated protein tau in DM rats and elucidate the role of GSK-3 and Akt (protein kinase B, PKB) in these processes. Streptozotocin injection-induced DM rats displayed an increased GSK-3 activity, decreased activity and expression of Akt. And Aβ40 and Aβ42 were found overproduced and the microtubule-associated protein tau was hyperphosphorylated in the hippocampus. Furthermore, selective inhibition of GSK-3 by lithium could attenuate the conditions of Aβ overproduction and tau hyperphosphorylation. Taken together, our studies suggest that GSK-3 regulates both the production of Aβ and the phosphorylation of tau in rat brain and may therefore contribute to DM caused AD-like neurological defects.